GAMBARAN STRES PENGASUHAN ORANG TUA YANG MEMILIKI ANAK TUNAGRAHITA DI SEKOLAH LUAR BIASA NEGERI 1 DENPASAR - Wulandari, Ni Putu Cintya; Utami, Kadek Cahya; Nurhesti, Putu Oka Yuli; Puspita, Luh Mira (Coping: Community of Publishing in Nursing; Vol 12 No 4 (2024): Agustus 2024, 2025)
Intellectual disabilities is a disorder of adaptive behavior and intellectual function that is below average. The condition of child with intellectual disabilities causes parents to experience problems in parenting because they have more duties and responsibilities than caring for normal children. Parenting problems experienced by parents if they continues can cause parents to feel parenting stress. The aim of this study was to elucide the explanation for parenting stress in parents with children with intellectual disabilities in SLB Negeri 1 Denpasar. This study was a descriptive study with a cross-sectional approach. Respondents in this study was 43 parents of children with intellectual disabilities from SLB negeri 1 Denpasar who were selected using a total sampling technique. The result of this study was found the parents are mainly female (55,8%), aged between 36-45 (55,8%), and graduated from high school or vocational school (60,5%). A statistical test showed that most parents had moderate parenting stress, with 28 of them (65,1%). The conclusion of this study is that the parenting stress experienced by parents of children with intellectual disabilities in SLB Negeri 1 Denpasar is mostly moderate parenting stress.